Exploration of Gen Z's Personal Financial Management Strategies in the Digital Era - Astuti Setianingsih, Puji; Hadi Isnanto, Samto (Dinasti International Journal of Digital Business Management, 2025)
This inquire about points to investigate individual monetary administration procedures by Era Z (Gen Z) within the advanced time. The center of the investigate is on the utilize of advanced innovation, moral mindfulness, and individual values in money related decision-making. Gen Z tends to utilize computerized budgetary applications and venture stages. The inquire about employments a graphic subjective approach to distinguish challenges and dangers. Whereas innovation makes it simple, computerized showcasing and information security issues stay vital issues. Moral mindfulness and individual values too play a part in their monetary choices. The research is anticipated to supply experiences for computerized budgetary administrations and arrangements that are more reasonable for Gen Z.